Comparative Analysis of Transposable Elements Highlights Mobilome Diversity and Evolution in Vertebrates - Chalopin, Domitille (Genome Biol Evol, 2015)
Transposable elements (TEs) are major components of vertebrate genomes, with major roles in genome architecture and evolution. In order to characterize both common patterns and lineage-specific differences in TE content and TE evolution, we have compared the mobilomes of 23 vertebrate genomes, including 10 actinopterygian fish, 11 sarcopterygians, and 2 nonbony vertebrates. We found important variations in TE content (from 6% in the pufferfish tetraodon to 55% in zebrafish), with a more important relative contribution of TEs to genome size in fish than in mammals. Some TE superfamilies were found to be widespread in vertebrates, but most elements showed a more patchy distribution, indicative of multiple events of loss or gain. Interestingly, loss of major TE families was observed during the evolution of the sarcopterygian lineage, with a particularly strong reduction in TE diversity in birds and mammals. Phylogenetic trends in TE composition and activity were detected: Teleost fish genomes are dominated by DNA transposons and contain few ancient TE copies, while mammalian genomes have been predominantly shaped by nonlong terminal repeat retrotransposons, along with the persistence of older sequences. Differences were also found within lineages: The medaka fish genome underwent more recent TE amplification than the related platyfish, as observed for LINE retrotransposons in the mouse compared with the human genome. This study allows the identification of putative cases of horizontal transfer of TEs, and to tentatively infer the composition of the ancestral vertebrate mobilome. Taken together, the results obtained highlight the importance of TEs in the structure and evolution of vertebrate genomes, and demonstrate their major impact on genome diversity both between and within lineages.